2013
DOI: 10.1002/ejic.201301102
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ligand Polarization on Asymmetric Structural Formation for Strongly Luminescent Lanthanide Complexes

Abstract: The effect of ligand polarization on the formation of strongly luminescent lanthanide complexes with asymmetric structures is described for the first time. The lanthanide complexes are composed of Eu III ions, three hexafluoroacetylacetonate (hfa) ligands, and two monodentate phosphine oxideligands,namely,triphenylphosphineoxide(TPPO), p-tolyldiphenylphosphine oxide (TPPO-Me), tri-p-tolylphosphine oxide (TPPO-3Me) or o-phenoxyphenyldiphenylphosphine oxide (TPPO-OPh). The luminescence properties of the Eu III c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 85 publications
1
29
0
Order By: Relevance
“…Lima et al has demonstrated that the distortion of coordination geometry of lanthanide ion leads to high emission quantum yields [7]. We have also reported that the asymmetric dodecahedron structure give rise to high k r [9]. These results indicate that the radiative transition probability between the 4f orbitals is enhanced by reducing the geometrical symmetry of the coordination structures.…”
Section: Introductionsupporting
confidence: 60%
See 1 more Smart Citation
“…Lima et al has demonstrated that the distortion of coordination geometry of lanthanide ion leads to high emission quantum yields [7]. We have also reported that the asymmetric dodecahedron structure give rise to high k r [9]. These results indicate that the radiative transition probability between the 4f orbitals is enhanced by reducing the geometrical symmetry of the coordination structures.…”
Section: Introductionsupporting
confidence: 60%
“…The Tb(III) cluster also contain systematic intramolecular CH-π and π-π interactions. The intramolecular interactions can be changed using alkyl salicylate derivatives that affects coordination geometry of Tb(III) ions [7,9,11]. In terms of the photophysical properties coordination geometry has strong relationship with photophysical properties.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the emission lifetime of the spin‐coated [Eu(hfa) 3 (dppcz)] n thin film (longer component: 0.46 ms) was different to that of [Eu(ntfa) 3 (dppcz)] n powder and nanosized [Eu(ntfa) 3 (dppcz)] n on a glass electrode. In general, the decomposition of an asymmetric eight‐coordinate structure of a lanthanide coordination compound leads to 1) a decrease of the I rel value, 2) a decrease of the radiative rate constant, and 3) an increase in the emission lifetime . The larger emission lifetime of the spin‐coated [Eu(hfa) 3 (dppcz)] n thin film might be due to decomposition of the coordination structure.…”
Section: Resultsmentioning
confidence: 99%
“…With the increase of heating temperature, the intensities of the emission band are enhanced and reach to the maximum at 502 nm for the sample D. [30][31][32]. It led to more charges being delocalized on B-O bonds, which is directly related to the electric dipole of hypersensitive transition and environmental of luminescent centers [33]. The probability of electric transfer from 2p state of O 2-to 3s state of B 3? are increased that has resulted in tunable emission peaks from A to E samples with exhibiting a red shift [12,17,18], which is consist with the previous reports.…”
Section: Luminescent Propertiesmentioning
confidence: 99%